Pengembangan Kompetensi Pelaku Usaha Mikro Kecil Menengah Kelurahan Purwodiningratan Surakarta Guna Mewujudkan Digital Preneur - Veronika, Prima; Ramadhani, Navadilla; Ragacitta, Nareswari Rineka; Prabandaru, Nirmana Ratri; Firdausi, Nabila Nuzulla; Taib, Nabil Abdurrahman; Tamelia, Nurdina; Naharunna, Nana; Ibrahim, Syahlaa’ Shoofi; Rahmawati, Aditya Nur; Djatunnisa, Ifa (Adi Widya : Jurnal Pengabdian Masyarakat, 2025)
This UMKM socialization activity aims to develop the digital competence of UMKM actors in order to create digital entrepreneurs who can compete with the complex dynamics of today's market. With the digitalization of UMKM actors, It is anticipated that UMKM owners will recognize the significance of strengthening their understanding of financial management, marketing strategies, and the application of appropriate technology, so that they can position their businesses effectively and efficiently. This activity uses the Lecture and Drill and Practice methods which can attract the public to join in the activity. The data from this study reveals, (1) The socialization of UMKM digitalization provides benefits for the development of UMKM businesses in Purwodiningratan Village, (2) Increases digital competence for UMKM actors in the use of digital marketing platforms such as: marketplaces, digital payment methods using QR Code scans (QRIS), and digital financial records, and (3) UMKM actors are able to practice making digital payments in the form of QR Codes (QRIS) independently so that digital entrepreneurs can develop in Purwodiningratan Village.